2001
DOI: 10.1177/00912700122010474
|View full text |Cite
|
Sign up to set email alerts
|

Role of Veterinary Medicine in Public Health: Antibiotic Use in Food Animals and Humans and the Effect on Evolution of Antibacterial Resistance

Abstract: Veterinary public health is another frontier in the fight against human disease. The veterinary public health scope includes the control and eradication of zoonoses, diseases that are naturally transmitted between vertebrate animals and man. These diseases pose a continuous hazard to the health and welfare of the public. More than 100 diseases are categorized as zoonoses, including salmonellosis. It is important to understand how antibiotics are used in humans and in food animals and how these uses affect the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
31
0
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 5 publications
5
31
0
2
Order By: Relevance
“…This agrees with previous research from across the veterinary sector (Hughes and others 2012, 2013, Williams and others 2012). Farmers considered their vet to be the most trustworthy source of information on antimicrobials as is shown by previous research which confirmed the strong reliance that farmers place on vets for information (Lathers 2001, Ruegg 2006, Friedman and others 2007). Advertising by pharmaceutical companies was not considered to influence prescribing behaviour by either the vet or farmer focus groups.…”
Section: Discussionsupporting
confidence: 63%
“…This agrees with previous research from across the veterinary sector (Hughes and others 2012, 2013, Williams and others 2012). Farmers considered their vet to be the most trustworthy source of information on antimicrobials as is shown by previous research which confirmed the strong reliance that farmers place on vets for information (Lathers 2001, Ruegg 2006, Friedman and others 2007). Advertising by pharmaceutical companies was not considered to influence prescribing behaviour by either the vet or farmer focus groups.…”
Section: Discussionsupporting
confidence: 63%
“…However, the emergence of extended-spectrum β-lactamase enzymes and decreased susceptibility to ciprofloxacin in Salmonella strains has drastically reduced the treatment options, which may lead to unfavorable outcomes [9,10]. In veterinary medicine, the use of antimicrobial drugs for therapeutic purposes and as growth promoters may stimulate the selection of antimicrobial-resistant Salmonella strains [11,12], causing a major public health concern.…”
Section: Smentioning
confidence: 99%
“…Therefore, understanding the epidemiology of antibacterial resistance will enable us to develop preventive strategies to limit existing resistance and to avoid the emergence of new strains of resistant bacteria. [50,51]. use of antibiotics for food animals and development of guidelines, codes of practice and policies on appropriate use of antibiotics.…”
Section: Control Of Resistance For Vancomycinmentioning
confidence: 99%